2010
DOI: 10.5194/acp-10-647-2010
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from transport, solid fuel burning and cooking to primary organic aerosols in two UK cities

Abstract: Abstract. Organic matter frequently represents the single largest fraction of fine particulates in urban environments and yet the exact contributions from different sources and processes remain uncertain, owing in part to its substantial chemical complexity. Positive Matrix Factorisation (PMF) has recently proved to be a powerful tool for the purposes of source attribution and profiling when applied to ambient organic aerosol data from the Aerodyne Aerosol Mass Spectrometer (AMS). Here we present PMF analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
385
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(461 citation statements)
references
References 81 publications
70
385
6
Order By: Relevance
“…These factors usually have similar mass spectra but different size distributions and time series (Fig. S6 in (Allan et al, 2010;, our solutions within the same family show less variation than in the reported 2-D cases. The variation among the solutions in each family is quite small.…”
Section: Figsupporting
confidence: 51%
See 1 more Smart Citation
“…These factors usually have similar mass spectra but different size distributions and time series (Fig. S6 in (Allan et al, 2010;, our solutions within the same family show less variation than in the reported 2-D cases. The variation among the solutions in each family is quite small.…”
Section: Figsupporting
confidence: 51%
“…We calculate each solution from 50 different starting seeds and then compare these solutions ). The 50 solutions can be grouped into "families" of solutions by comparing Q/Q exp values and the similarity of factors within the family (Allan et al, 2010;. Each family can then be represented by the average of the solutions in that family, and one family can be selected as the best solution.…”
Section: Guidelines For Choosing a Solutionmentioning
confidence: 99%
“…Shown in Figure 7b is a scatter plot of the CO and the HOA + CIOA data. The improved correlation when the CIOA mass concentration is added to the HOA mass concentration is surprising because cooking is not considered a major source of carbon monoxide, although it is a significant source of organic aerosol [Allan et al, 2010; California Air Resources Board, California emission inventory data, 2008, http://www.arb.ca.gov/ei/ emsmain/emsmain.htm; Harley et al, 1997]. Emissions of CO have been measured from certain cooking activities [Lee et al, 2001], but it is still a possibility that the CIOA component contains particulate mass from noncooking sources that also emit CO (e.g., gasoline vehicles).…”
Section: Evaluation Of Primary Organic Aerosol Emission Ratios With Ementioning
confidence: 99%
“…The results of PMF illustrate that rBC-and HOA-rich factors accounted for about 60 and 20 wt % of rBC with a thin coating, respectively, and the rBC-rich factor contributed about 82 wt % of the freshly emitted rBC from traffic, similar to previous observations in the roadside environment . The COA factor is commonly observed in urban areas (Allan et al, 2010;Mohr et al, 2012) but its mixing with ambient rBC is seldom reported. The absence of a COA factor in rBC-containing particles highlights the fact that emissions of rBC from modern kitchens and the mixing of rBC and COA through particle coalescence were negligible in this study.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%